THE OCCURRENCE AND SEQUENCE ANALYSIS OF MILKY HEMOLYMPH DISEASE IN LOBSTER PANULIRUS HOMARUS FROM DIFFERENT LOCATIONS IN INDONESIA - Sudewi Sudewi; Zeny Widiastuti; Ida Komang Wardana; Ketut Mahardika (Journal of Aquaculture and Fish Health, 2020)
Among the high significance diseases in spiny lobster farming, Milky Hemolymph Disease of Spiny Lobster (MHD-SL) is considered as the most devastating disease which caused in mortality up to 80 % and morbidity to 100%. Investigations of this disease were mostly performed for farmed lobster and no observation was conducted for wild lobster. This study was carried out first, to investigate milky hemolymph disease occurrence both in wild and farmed spiny lobster Panulirus homarus from different locations by PCR analysis. Second, to perform nucleotide sequence analysis in order to identify, and to describe relationship of the milky disease agent obtained in this study with the disease agent from several geographical regions by phylogenetic analysis. Adult farmed lobsters were collected from Lombok, Pangandaran and Pegametan, while wild lobsters were obtained from Jembrana, Lombok, and Banyuwangi coastal areas. One farmed lobster from Pegametan and two farmed lobsters from Lombok were infected with the milky disease. Nucleotide sequence analysis demonstrated that the causative agent of milky disease obtained in this study (MHD-1, 2, and 3) exhibited 99% homologous nucleotide sequence with milky disease agent from Vietnam that was uncultured Rickettsia-like Bacteria (RLB). As a consequence, further work is needed most importantly on how to cultivate milky disease agent in order to find proper methods to alleviate milky disease problems. This paper is the first report on phylogenetic analysis of milky disease from Indonesia that pointed out a closed relationship between milky disease in the present study and from Vietnam, Madagascar, Mozambique and Tanzania.